Current trends in the development of sport fishing in the Dnipropetrovsk region - Ageenko, І.; Агеєнко, І. М.; Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; Novickij, R. A.; Novitskyy, R. O.; et al. (Інститут рибного господарства Національної академії аграрних наук України, 2025)
The data on the development and current state of sport fishing in the Dnipropetrovsk region were collected as a result of long-term studies and observations (2003– 2024). Data collection and processing was based on generally accepted basic methods of recreational fishing research. The information was collected by direct inspection of fisherman’s catches during competitions and questionnaires. Original author’s data and materials of the Federation of Fishing Sports of Ukraine were used. A total of 29 Cups and Championships of the regional and national levels were analyzed. A total of 1068 catches of sport fishermen were studied. The obtained material was analyzed and subjected to statistical processing. В результаті багаторічних досліджень і спостережень (2003–2024 рр.) зібрано дані про розвиток і сучасний стан спортивного рибальства в Дніпропетровській області. Збір та обробку даних проводили на основі загальноприйнятих базових методик досліджень рекреаційного рибальства. Інформацію збирали методами безпосереднього огляду уловів рибалок-спортсменів під час змагань та анкетування. Використані оригінальні авторські дані та матеріали Федерації риболовного спорту України. Всього проаналізовано 29 кубків та чемпіонатів обласного та всеукраїнського рівня. Досліджено 1068 уловів рибалок-спортсменів. Отриманий матеріал аналізували і піддавали статистичній обробці.
Сучасні тенденції розвитку спортивного рибальства в Дніпропетровській області
Новіцький Роман Олександрович https://orcid.org/0000-0001-9373-5759
Keywords: Ukraine; Україна; Prydniprovia; Придніпров’я; fishing; рибальство; sport fishing; риболовний спорт; sports disciplines; спортивні дисципліни; sport fishermen; рибалки-спортсмени; catch accounting; облік уловів; sports achievements; спортивні досягнення; development; розвиток